Slope-intercept form of equation of the line:
y = mx + b
y = -x + 6 ⇒ slope m₁ = -1
perpendicular line's slope:
![m_2=(-1)/(m_1) = (-1)/(-1)=1](https://img.qammunity.org/2023/formulas/mathematics/high-school/73uvg74ygrxgm2npcaizzw9y6wihk4dy0l.png)
If line of equation y = mx + b passes through a ponit (x₀, y₀) then equation: y₀ = mx₀ + b is true.
So:
2 = 1×(-4) + b
2 = -4 + b
b = 6
Therefore:
The equation in slope-intercept form for the line that passes through the point (-4, 2) and is perpendicular to the graph of the equation y=-x+6 is:
y = x + 6